1991
DOI: 10.1177/019791839102500203
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Significance of Ethnic and Class Resources in Immigrant Businesses: The Case of Korean Immigrant Businesses in Chicago

Abstract: Contemporary Korean immigrant businesses depart from the traditional patterns of immigrant businesses in two important respects. First, minority areas such as black neighborhoods are more important market places for Korean merchants than their own Korean community. Second, though ethnic solidarity and mutual cooperation among Koreans are still viable in Korean immigrant businesses, class interests and class resources are increasingly important as the basis of Korean immigrant businesses. Therefore, collective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…Korean immigrants maintain strong ethnic social ties through organizations such as churches. However, they have no powerful intermediate ethnic organizations that effectively coordinate and regulate economic activities, sometimes leading to intra-ethnic competition and price wars, decreasing profit margins and threatening business survival (Kim and Hurh, 1985;Yoon, 1991).…”
Section: Culture's Influence On Ethnic Entrepreneurial Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Korean immigrants maintain strong ethnic social ties through organizations such as churches. However, they have no powerful intermediate ethnic organizations that effectively coordinate and regulate economic activities, sometimes leading to intra-ethnic competition and price wars, decreasing profit margins and threatening business survival (Kim and Hurh, 1985;Yoon, 1991).…”
Section: Culture's Influence On Ethnic Entrepreneurial Orientationmentioning
confidence: 99%
“…Korean immigrant businesses rely heavily on family labor. Many spouses provide not only unpaid labor, but also function as business collaborators (Min, 1988;Yoon, 1991). About 21 percent of Korean immigrant entrepreneurs in Atlanta reported that adult children (over 16 years old) helped them with business after school and/or during weekends (Min, 1984).…”
Section: Human Capitalmentioning
confidence: 99%
“…Previous research regarding minority entrepreneurs has noted the prevalence of husbandwife business teams in Korean immigrant businesses (Nam and Herbert, 1999;Yoon, 1991). To the extent that non-immigrant Korean-American businesses follow this basic model, we expect to find greater spousal involvement in decision-making in this ethnic group.…”
Section: Family Role Demandsmentioning
confidence: 89%
“…More recently, questions have been raised about the role of RCAs as a key source of start‐up capital in light of evidence that the mobilization of start‐up capital for Korean immigrant businesses mostly comes from other sources – e.g. , personal savings, loans from kin or friends, bank loans, or money brought from Korea – not from RCAs in the Korean American community (Yoon, 1991, 1997; Min, 1996; Park, 1997; Lee, 2002). Moreover, among Korean immigrant merchants, RCAs have evolved gradually from serving economic functions toward mainly fueling a social and mutual aid role, like friendship RCAs in Korea (Kim, 1981; Park, 1997; Yoo, 2001).…”
Section: Korean Rotating Credit Associationsmentioning
confidence: 99%